Does aluminum impair photosynthetic performance when applied ‘directly’ on leaves? - de Oliveira Carvalho, Brenda Mistral [UNESP]; Silva, Giselle Schwab [UNESP]; Gavassi, Marina Alves [UNESP]; Habermann, Gustavo [UNESP] (Springer Nature, 2023)
Background and aims: The first symptom of aluminum (Al) toxicity is the inhibition of root growth, and it also reduces shoot growth and photosynthetic performance. Most of the absorbed Al is retained in the roots. Thus, it is unclear whether aboveground symptoms are consequence of the Al retained in the root or a direct effect of the minor Al concentration reaching the mesophyll. Here, we investigate whether Al ‘directly’ impairs photosynthetic performance. Methods: Two experiments were performed using ‘Mandarin’ lime (Citrus x limonia) cultivated in nutrient solution without Al: solution absent in Al and increasing Al concentrations were (1) injected into petioles for 24 h, and (2) sprayed daily on the leaves for 60 days. Gas exchange, photochemical responses, relative water content (RWC), biometric data, biomass, and Al concentration in the organs was evaluated. Results: Gas exchange and photochemical parameters decreased after Al injection. Plants sprayed with Al showed low shoot growth, CO2 assimilation (A), stomatal conductance (gs), and transpiration (E). Only plants sprayed with the highest Al concentration showed reduced photochemical parameters, low RWC, and increased root Al concentration. High A x gs and E x gs correlations were found at the end of both studies. Conclusion: Aluminum reduces the photosynthetic performance when applied directly on leaves. Low stomatal aperture seems to be more critical than photochemical performance to explain the low A, and the low gs could not be explained by low leaf hydration. Shoot-to-root translocation can be observed in plants sprayed with Al.
Keywords: Al foliar absorption; Al translocation; Al3+; Citrus x limonia; Shoot-to-root Al transport